A comprehensive review of nano-enhanced phase change materials on solar energy applications. (June 2022) - Shoeibi, Shahin; Kargarsharifabad, Hadi; Mirjalily, Seyed Ali Agha; Sadi, Meisam; Arabkoohsar, Ahmad
Abstract: More and more studies are today focusing on solar systems owing to the increasing awareness about global warming caused by conventional energy technologies and techno-economic advances of solar technologies. Due to the fluctuating essence of solar energy, the storage of solar energy (either electricity or thermal energy) is inevitable to make solar units reliable elements of complex energy systems. From a thermal energy angle, phase change materials (PCMs) have gained much attention as they not only offer a high storage capacity compared to sensible thermal storage methods in a very wide range of possible storage temperatures but also an acceptable state-of-practice which is a drawback of thermochemical storage approaches. Many research projects are being conducted on the enhancement of thermal characteristics of PCMs in solar systems in various methods, such as adding nanoparticles. These materials are so-called nano-enhanced PCMs facilitate charging and discharging processes of the heat storage units owing to their augmented thermal conductivities and reduced melting points. This article tries to make a comprehensive review of the latest studies conducted on nano-enhanced PCMs in a variety of solar technologies. The key yet concrete finding here is that the proposed methods in this framework may have a significant impact on solar systems from a technical point of view, but their practicality can sometimes be an issue. The article provides readers with a perspective of the topic and some suggestions for future research. Highlights: Nano-enhanced phase change material used to reduce the solar panel temperature. The melting point of phase change material was reduced with adding nanoparticles. The nano-enhanced phase change material enhances the electrical and thermal efficiency of PV/T. Graphene oxide nanoparticles mixed in paraffin has a significant effect on water productivity of solar still.